2019
DOI: 10.3390/met9121351
|View full text |Cite
|
Sign up to set email alerts
|

Laser Beam Welding of a Low Density Refractory High Entropy Alloy

Abstract: The effect of laser beam welding on the structure and properties of a Ti1.89NbCrV0.56 refractory high entropy alloy was studied. In particular, the effect of different pre-heating temperatures was examined. Due to the low ductility of the material, laser beam welding at room temperature resulted in the formations of hot cracks. Sound butt joints without cracks were produced using pre-heating to T ≥ 600 °C. In the initial as-cast condition, the alloy consisted of coarse bcc grains with a small amount of lens-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…To overcome the hot cracking problem, preheating was carried out between 600 and 800 • C. This provided sound butt joint welds. As the preheating temperature increased, the grain size increased, as shown in Figure 4 [57].…”
Section: Weldingmentioning
confidence: 91%
“…To overcome the hot cracking problem, preheating was carried out between 600 and 800 • C. This provided sound butt joint welds. As the preheating temperature increased, the grain size increased, as shown in Figure 4 [57].…”
Section: Weldingmentioning
confidence: 91%
“…There are further studies on welding of HEAs/CCAs by special processes such as explosion welding [35], diffusion welding [36], and individual examinations on refractory HEAs [37]. These investigations will not be discussed in the following, as this overview focuses on basic welding properties of the equiatomic CoCrFeMnNi HEA ("Cantor" alloy in accordance with [6]) and various compositions of the Al x CoCrCu y FeNi (with 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1) HEAs/ CCAs [38][39][40].…”
Section: Hea Typesmentioning
confidence: 99%
“…Several studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] have already been reported on fusion-based welding of HEAs. To date, these works focus mainly on laser-based techniques, although some information is also available on Electron Beam and Gas Tungsten Arc Welding (GTAW) techniques.…”
Section: Fusion-based Welding Of Heasmentioning
confidence: 99%
“…Panina et al [69] reported the effects of pre-heating temperature (400, 600, and 800 • C) on the laser weldability of a Ti 1.89 NbCrV 0.56 refractory high entropy alloy. Initially, the BM microstructure was mainly composed by BCC grains presenting also small C15 Laves phase particles.…”
Section: Other Hea Systemsmentioning
confidence: 99%